Five new limonoids isolated from Walsura robusta - Li Hou; Cui-Xuan Mei; Chun-Mao Yuan; Gui-Hua Tang; Duo-Zhi Chen; Qing Zhao; Hong-Ping He; Ming-Ming Cao; Xiao-Jiang Hao (Natural Products and Bioprospecting, 2023)
Abstract Five new toosendanin limonoids with highly oxidative furan ring walsurobustones A-D (1–4), and one new furan ring degraded limonoid walsurobustone E (5) together with one known compound toonapubesic acid B (6) were isolated from the leaves of Walsura robusta. Their structures were elucidated by NMR and MS data. Especially, the absolute configuration of toonapubesic acid B (6) was confirmed by X-ray diffraction study. Compounds 1–6 exhibited good cytotoxicity against the cancer cell lines HL-60, SMMC-7721, A-549, MCF-7, and SW480.